Validated RP-HPLC Method with UV Detection for the Determination of Cinitapride in its Formulation and Human Plasma - Tulasamma, P.; Venkateswarlu, P. (Asian Journal of Chemistry, 2012)
A novel, simple method for the determination of cinitapride hydrogen tartrate in human plasma by reversed phase liquid chromatography with UV detection at 260 nm. The method was developed using Hypersil BDS C18 (250 × 4.6 mm, 5 μm) column with mobile phase containing a mixture of acetonitrile: buffer (55:45 v/v), pH adjusted to 3 with 0.02 M mixed phosphate buffer. The method is sensitive with limit of quantification of 0.523 ng mL-1. The calibration plot for cinitapride in spiked plasma was linear in the concentration range 25-150 ng mL-1. The chromatographic conditions are flow rate of 1 mL min-1, column temperature 30 ºC and the retention time was 4.233 min for cinitapride. The developed method was validated as per international conference harmonization (ICH) guidelines with respect to specificity, limit of detection, limit of quantitation, precision, accuracy robustness and system suitability. The method is also suitable for the assay of cinitapride which ranged from 97 % to 100 %. The method can be successfully used for analysis of cinitapride in its formulation and human plasma during pharmacokinetic studies.